Quantification of Formaldehyde Residue in Wet Noodles Marketed in Indonesia using RP-HPLC Derivatization Method - Mutakin Mutakin; Renyiska Yula; Ida Musfiroh; Nuraeni Nuraeni; Nurdjanah Azinar; Jutti Levita (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Illegal practices of formaldehyde as preservatives in wet noodles have been proven. These formaldehyde-preserved wet noodles are sold in West Java, Indonesia. This compound may be harmful to the body due to a decreasing of blood pressure, coma, acidosis, and acute renal failure. In this study we proposed a quantification method using high performance liquid chromatography (HPLC). A simulation was carried out as comparison. This simulation comprised of formaldehyde-spiked fish then the process was continued by washing, frying, and distilling the fish in a closed-system distillation. Similar condition was applied onto wet noodles purchased from traditional markets in Bandung. Method used was RP-HPLC derivatization method based on the reaction of formaldehyde carbonyl with two different reagents of DNPH (2,4-dinitrophenylhydrazine) and Nash (acetyl acetone, ammonium acetate and acetic acid) reagents. Result showed that formaldehyde residue was detected and quantified in all wet noodle samples with a range of 21-59 ppm. In conclusion, this method can be used for routine analysis to control illegal practices of formaldehyde in wet noodles. Moreover, washing and frying the formaldehyde-preserved food were proven could significantly help reducing formaldehyde level in food.Keywords: 2,4-dinitrophenylhidrazine, formaldehyde, RP-HPLC, wet noodles